2018
DOI: 10.2337/dc17-1144
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy Effect in Type 2 Diabetes: Impact of Early Glycemic Control on Future Complications (The Diabetes & Aging Study)

Abstract: Among patients with newly diagnosed diabetes and 10 years of survival, HbA levels ≥6.5% (≥48 mmol/mol) for the 1st year after diagnosis were associated with worse outcomes. Immediate, intensive treatment for newly diagnosed patients may be necessary to avoid irremediable long-term risk for diabetic complications and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
334
2
36

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 442 publications
(382 citation statements)
references
References 26 publications
10
334
2
36
Order By: Relevance
“…The interaction between diabetes duration and glycaemic control on the risk of death that we report could potentially also explain the inconsistencies between previous observational studies on older patients with T2D, which have reported both linear 32,33 and nonlinear relationships 30,34,35 between levels of glycaemia and mortality risk. Although the present study does not allow for causal inference due to its observational design, our results suggest that aiming for normoglycaemic levels in those with short duration of diabetes may be beneficial, whereas for individuals with long diabetes duration, setting universal goals may be less straightforward.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The interaction between diabetes duration and glycaemic control on the risk of death that we report could potentially also explain the inconsistencies between previous observational studies on older patients with T2D, which have reported both linear 32,33 and nonlinear relationships 30,34,35 between levels of glycaemia and mortality risk. Although the present study does not allow for causal inference due to its observational design, our results suggest that aiming for normoglycaemic levels in those with short duration of diabetes may be beneficial, whereas for individuals with long diabetes duration, setting universal goals may be less straightforward.…”
Section: Discussioncontrasting
confidence: 68%
“…Previous studies on middle-aged patients with T2D have shown conflicting results concerning the relationship between glycaemic control, diabetes duration and mortality risk. For instance, in a recent study by Laiteerapong et al 34 the authors found that newly diagnosed middle-aged patients with tight glycaemic control (6.5% [<48 mmol/mol ]) had the lowest mortality risk, with increasing effect sizes with longer exposure to poor glycaemic control. 34 As opposed to our results on elderly patients, they found no increased mortality risk in the normoglycaemic range with increasing duration of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent analysis of 271 174 patients with type 2 diabetes (T2D) registered in the Swedish National Diabetes Register showed that HbA1c >7% tracks much more strongly with mortality and cardiovascular disease (CVD) outcome among people with T2D than do blood pressure or low‐density lipoprotein cholesterol . The Kaiser Permanente Northern California Diabetes Registry of 34 737 people followed for at least a decade (mean 13 years; mean age at diagnosis 57 years) found those with mean HbA1c ranging from 7.0% to <8.0% and those with HbA1c ≥9.0% had approximately 40% and 120% higher subsequent microvascular event rates, respectively, and approximately 30% and 50% higher macrovascular event rates, than those with mean HbA1c <6.5% during the first year after diagnosis . Both high HbA1c groups had approximately 30% higher mortality than those with the lower HbA1c levels .…”
mentioning
confidence: 99%
“…The Kaiser Permanente Northern California Diabetes Registry of 34 737 people followed for at least a decade (mean 13 years; mean age at diagnosis 57 years) found those with mean HbA1c ranging from 7.0% to <8.0% and those with HbA1c ≥9.0% had approximately 40% and 120% higher subsequent microvascular event rates, respectively, and approximately 30% and 50% higher macrovascular event rates, than those with mean HbA1c <6.5% during the first year after diagnosis . Both high HbA1c groups had approximately 30% higher mortality than those with the lower HbA1c levels . The implication of this and many other studies that better glycemic control is beneficial for people with T2D is inescapable.…”
mentioning
confidence: 99%